Preparation method and application of low breakage rate rice line special modified starch ingredient

CN122997329APending Publication Date: 2026-10-30HARBIN UNIV OF COMMERCE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611243507.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-17
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

而目前现有淀粉酶法改性技术多采用单一酶处理方式,主要通过改变淀粉直链/支链比例、分子链长分布或糊化特性实现品质调控,但调控效果相对单一,难以同时兼顾米线的结构稳定性、弹韧性及口感特征

Benefits of technology

[0020]采取上述技术方案有益效果包括:本发明提供一种低断条率米线专用改性淀粉的制备方法,通过普鲁兰酶-转葡萄糖苷酶(PUL-TG)复合改性玉米淀粉,并将其应用于米线制备中,有效改善了传统米线蒸煮品质差、易断条、口感松软及食用品质不佳等问题。通过调控淀粉分子链结构及支化特性,提高了淀粉分子间相互作用能力,使制备得到的米线具有更好的结构稳定性和质构特性。其中,添加3%的PUL-TG改性玉米淀粉(脱支处理6 h)制备的米线表现出最佳品质,蒸煮损失率和断条率显著降低,米线完整性提高,同时具有适宜的硬度、弹性、咀嚼性及爽滑口感,使米线具有更优的食用品质和加工适应性。本发明所制备的改性淀粉配料常温贮藏12个月内理化品质稳定,无明显酸败。本发明提供的改性淀粉配料工艺绿色安全、原料易得、效果显著,可用于高品质米线及其他淀粉类食品的加工生产,无需额外添加胶体、增稠等食品添加剂,可有效解决传统米线易断条、混汤、口感差等缺陷。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122997329A_ABST
    Figure CN122997329A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of food processing, in particular to a preparation method and application of a low-broken-ratio rice noodle special modified starch formula, the starch is used as raw material, a complex enzymolysis process of pre-debranching by using pullulanase and rebranching by using transglucosidase is adopted to modify the starch, the modified starch has the characteristics of high swelling power, low solubility, uniform molecular chain distribution and reasonable branch structure, etc., the modified starch is added into rice powder in a proportion of 3% to 7% to prepare rice noodles, the broken-ratio and the cooking loss rate of the rice noodles can be obviously reduced, the texture indexes such as hardness, elasticity and chewiness of the product are optimized, and the sensory quality and the microstructure stability are improved. The process is green and safe, raw materials are easy to obtain, and the effect is remarkable, and the process can be used for the processing and production of high-quality rice noodles and other starch foods.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of food processing technology, specifically to a method for preparing and applying a modified starch for rice noodles with low breakage rate. Background Technology

[0002] Rice noodles, a traditional Chinese grain food, enjoy strong market demand due to their smooth texture, convenience, and unique flavor. However, rice noodles are prone to breaking and becoming mushy during processing and consumption, exhibiting poor product structural stability. They also suffer from issues such as a sticky texture, insufficient elasticity, and poor smoothness, making it difficult to meet consumers' demands for high-quality staple foods. To improve rice noodle quality, adding suitable quality improvers has become an important technical means to enhance rice noodle processing performance.

[0003] Starch, as the main component in rice noodles that forms the gel structure and determines the final quality, directly affects the processing performance and eating quality of rice noodles due to its molecular structure characteristics. Natural starch, with its relatively simple molecular structure, results in insufficient gel network strength after gelatinization, leading to weak shear resistance and poor cooking performance, making it difficult to meet the requirements of high-quality rice noodle processing. Regulating the molecular structure of starch through starch modification technology to improve its physicochemical properties is currently an important method for optimizing the quality of rice and noodle products. Among these methods, enzymatic modification has advantages such as mild reaction conditions, green and safe operation, high selectivity, and easy control of the modification degree, making it an important technological direction in the field of food starch modification. However, current starch enzymatic modification technologies mostly use single enzyme treatment methods, primarily achieving quality control by changing the ratio of straight to branched starch chains, molecular chain length distribution, or gelatinization characteristics. However, the control effect is relatively singular, making it difficult to simultaneously address the structural stability, elasticity, and mouthfeel characteristics of rice noodles. For example, while using pullulanase alone for debranching can increase the proportion of linear starch chains and improve gel strength, excessive debranching can easily lead to increased rigidity of the starch system, resulting in products with excessive hardness and insufficient toughness.

[0004] Therefore, starch improvers that can synergistically improve the cooking stability, texture and sensory quality of rice noodles, while effectively reducing breakage rate and cooking loss rate, have become a pressing technical problem to be solved. Summary of the Invention

[0005] In view of the problems existing in the prior art, the present invention provides a method for preparing modified starch for rice noodles with low breakage rate and its application.

[0006] The technical solution of the present invention to solve the above-mentioned technical problems is as follows:

[0007] A method for preparing a modified starch ingredient for rice noodles with low breakage rate includes the following steps:

[0008] (1) Starch is dispersed in sodium acetate buffer solution to prepare a starch aqueous suspension, gelatinization is completed, and the mixture is cooled to obtain starch paste;

[0009] (2) Add pullulanase to the starch paste, stir and react for 4-8 h, heat in a boiling water bath for 10 min after the reaction is complete, and adjust the pH of the system with sodium hydroxide solution.

[0010] (3) Add transglucosidase to step (2) and react for 2-10 h. After the reaction is complete, heat in a boiling water bath for 10 min to obtain inactivated starch liquid.

[0011] (4) Add anhydrous ethanol to the inactivated starch liquid, stir and let stand at room temperature, then centrifuge, wash, freeze dry and grind to obtain modified starch ingredients;

[0012] Furthermore, the starch is one or more of corn starch, tapioca starch, potato starch, and mung bean starch.

[0013] Furthermore, the sodium acetate buffer solution had a concentration of 0.02 mol / L and a pH of 5.2.

[0014] Furthermore, the gelatinization temperature was 100℃ and the gelatinization time was 40 min.

[0015] Furthermore, in step (4), the centrifugation conditions are 3500 × g and centrifugation for 15 min.

[0016] Furthermore, in step (4), anhydrous ethanol is used for washing, and the number of washing cycles is 3-5.

[0017] This invention provides a method for preparing modified starch ingredients for rice noodles with low breakage rate.

[0018] This invention also provides an application of a modified starch ingredient for rice noodles with low breakage rate in the food industry.

[0019] Furthermore, it is applied to the preparation of rice noodles with low breakage rate, with the amount of modified starch added being 3% to 7% of the total mass of rice flour.

[0020] The beneficial effects of adopting the above technical solution include: This invention provides a method for preparing a modified starch specifically for rice noodles with low breakage rate. By modifying corn starch with pullulanase-transglucosidase (PUL-TG) and applying it to rice noodle preparation, it effectively improves the problems of poor cooking quality, easy breakage, soft texture, and poor eating quality of traditional rice noodles. By regulating the starch molecular chain structure and branching characteristics, the interaction ability between starch molecules is improved, resulting in rice noodles with better structural stability and textural properties. Among them, rice noodles prepared with 3% PUL-TG modified corn starch (debranched for 6 hours) exhibit the best quality, with significantly reduced cooking loss and breakage rate, improved rice noodle integrity, and suitable hardness, elasticity, chewiness, and smooth texture, resulting in superior eating quality and processing adaptability. The modified starch ingredients prepared by this invention maintain stable physicochemical quality and show no obvious rancidity within 12 months of storage at room temperature. The modified starch formulation process provided by this invention is green and safe, uses readily available raw materials, and has significant effects. It can be used for the processing and production of high-quality rice noodles and other starchy foods without the need for additional food additives such as colloids and thickeners. It can effectively solve the defects of traditional rice noodles such as easy breakage, cloudy soup, and poor taste. Attached Figure Description

[0021] Figure 1 To illustrate the composition, structure, and chain length distribution of the modified starch of this invention, Figure A shows the amylose and amylopectin content of each group of modified starches, Figure B shows the chain length distribution of the original corn starch, Figures C, D, and E show the chain length distribution of corn starch after PUL enzymatic hydrolysis for 4 h, 6 h, and 8 h, respectively, and Figures F, G, and H show the chain length distribution of corn starch after PUL-TG enzymatic hydrolysis for 2 h, 6 h, and 10 h, respectively.

[0022] Figure 2 The branching degree of the modified starch of this invention;

[0023] Figure 3 The images show the gelatinization curves of different modified starches in this invention. A is the gelatinization curve of corn starch hydrolyzed by PUL enzyme, and B is the gelatinization curve of corn starch hydrolyzed by PUL-TG enzyme.

[0024] Figure 4 The rheological properties of different modified starches in this invention are shown. A, B, and C are the rheological properties of PUL-enzymatically hydrolyzed corn starch, and D, E, and F are the rheological properties of PUL-TG-enzymatically hydrolyzed corn starch, respectively.

[0025] Figure 5 The present invention describes the hydration properties of different modified starches.

[0026] Figure 6 The short-range order of different modified starches in this invention is represented by A, where A is the Fourier transform infrared spectrum of different modified starches, and B is the 1047 / 1022 cm⁻¹ spectrum of different modified starches. -1 and 1022 / 995 cm-1 The ratio of absorption peaks;

[0027] Figure 7 XRD patterns and relative crystallinity of different modified starches of this invention;

[0028] Figure 8 To illustrate the different modified starch granule morphologies of this invention, A, B, C, D, E, F, and G represent the starch granule morphologies of native corn starch (CS), PUL-4 h, PUL-6 h, PUL-8 h, PUL-TG-2 h, PUL-TG-6 h, and PUL-TG-10 h, respectively; where the numbers 1, 2, and 3 in each group represent the starch granule morphologies at magnifications of 1000x, 2500x, and 5000x, respectively.

[0029] Figure 9 The present invention provides the moisture content and fatty acid value of modified starches at different storage periods, where A represents the moisture content of modified starches at different storage periods, and B represents the fatty acid value of modified starches at different storage periods.

[0030] Figure 10 The cooking quality of extruded rice noodles with different modified starches in this invention is shown in the figure. In this figure, A is the breakage rate of different modified starches, B is the cooking loss, and C is the iodine blue value.

[0031] Figure 11 The short-range order of the extruded rice noodles with different modified starches in this invention is shown, where A and B are the Fourier transform infrared spectra of the extruded rice noodles with different modified starches, and C and D are the 1047 / 1022 cm⁻¹ spectra of the extruded rice noodles with different modified starches. -1 and 1022 / 995 cm -1 The ratio of absorption peaks;

[0032] Figure 12 The crystallization characteristics of extruded rice noodles with different modified starches according to the present invention;

[0033] Figure 13 Sensory scores for extruded rice noodles with different modified starches according to the present invention. Detailed Implementation

[0034] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0035] Unless otherwise specified, the reagents and materials used in this invention are all conventional reagents and materials in the art, which can be obtained commercially or prepared using conventional methods. Unless otherwise specified, the experimental methods used in this invention are all conventional experimental methods in the art.

[0036] The corn starch was purchased from Yantai Shuangta Food Co., Ltd., and is food grade.

[0037] See attached document Figure 1-13 This invention provides a method for preparing a modified starch ingredient for rice noodles with low breakage rate.

[0038] Example 1

[0039] Preparation method of PUL-TG modified starch ingredients

[0040] (1) Disperse 50g of corn starch in 0.02 mol / L sodium acetate buffer (pH 5.2) to prepare a 10% (w / v) aqueous suspension. Heat at 100℃ for 40 min to gelatinize it completely, and cool to 58℃ to obtain starch paste.

[0041] (2) Add 750 μL of pullulanase (PUL) with an enzyme activity of 4000 U / mL to the starch paste obtained in step (1), and carry out the debranching reaction for 6 h with continuous magnetic stirring. Then, place the reaction system in a boiling water bath and heat for 10 min to deactivate PUL. Use 1 mol / L NaOH solution to slowly adjust the pH of the system to 5.5.

[0042] (3) Add 1250 μL of transglucosidase (TG) with an enzyme activity of 12000 U / mL to the reaction solution in step (2) at 55℃ and continue the complex enzymatic hydrolysis reaction for 2 h. After the reaction is completed, heat it again in a boiling water bath for 10 min to deactivate TG and obtain inactivated starch liquid;

[0043] (4) Then add 3 times the volume of anhydrous ethanol to the inactivated starch liquid, stir continuously for 10 min, and let stand at room temperature for 30 min. Centrifuge at 3500 ×g for 15 min, collect the precipitate, wash with anhydrous ethanol 3-5 times, freeze dry, pulverize, and pass through a 100-mesh sieve to obtain PUL-TG modified starch, denoted as PUL-TG-2h.

[0044] Example 2

[0045] The difference between Example 2 and Example 1 is that the reaction time for the compound enzymatic hydrolysis reaction in step (3) is 6 hours. All other steps are the same, and PUL-TG modified starch is obtained, which is denoted as PUL-TG-6h.

[0046] Example 3

[0047] The difference between Example 3 and Example 1 is that the reaction time for the compound enzymatic hydrolysis reaction in step (3) is 10h, while the rest of the steps are the same, denoted as PUL-TG-10h.

[0048] Comparative Example 1

[0049] Preparation method of PUL modified starch ingredients

[0050] 50 g of corn starch (CS) was dispersed in 0.02 mol / L sodium acetate buffer (pH 5.2) to prepare a 10% (w / v) aqueous suspension. The suspension was heated at 100 °C for 40 min to allow for complete gelatinization. The suspension was then cooled to 58 °C, and 750 μL of PUL (4000 U / mL enzyme activity) was added. The mixture was then subjected to a debranching reaction under magnetic stirring for 4 h. After the reaction was complete, the system was placed in a boiling water bath for 10 min to terminate the enzyme reaction. Once the system had cooled to room temperature, three times the volume of anhydrous ethanol was added, and the mixture was stirred continuously for 10 min, then allowed to stand at room temperature for 30 min. The mixture was then centrifuged at 3500 × g for 15 min, and the precipitate was collected and washed 3-5 times with anhydrous ethanol. The precipitate was dried, pulverized, and passed through a 100-mesh sieve to obtain PUL-modified starch, denoted as PUL-4h.

[0051] Comparative Example 2

[0052] The difference between Comparative Example 2 and Comparative Example 1 is that the debranching reaction takes 6 hours, while the other steps are the same, denoted as PUL-6h.

[0053] Comparative Example 3

[0054] The difference between Comparative Example 3 and Comparative Example 1 is that the debranching reaction time is 8 hours, while the other steps are the same, denoted as PUL-8h.

[0055] Performance testing

[0056] The PUL-modified starch and PUL-TG-modified starch prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to the following performance tests, and are collectively referred to as modified starch.

[0057] 1. Determination of modified starch composition: The amylose and amylopectin contents in modified starch and corn starch were determined using an amylose / amylose kit, and the results are expressed as mass fraction (%, w / w).

[0058] 2. Determination of modified starch chain length distribution: Accurately weigh 5 mg of modified starch, resuspend it in 0.9 mL of deionized water, heat in a boiling water bath for 15 min, and vortex intermittently to mix. Then add 0.1 mL of 0.1 M sodium acetate (pH 3.5), 35 mL of NaN with a concentration of 40 mg / mL, and 10 μL of isoamylase with an enzyme activity of 1400 U. Incubate at 37 °C for 3 h. After that, add 5 mL of anhydrous ethanol, centrifuge at 4000 × g for 10 min to obtain a precipitate, and add 1 mL of DMSO / LiBr (1:1) solution to the precipitate. Dissolve the precipitate at 80 °C and 350 rpm for 2 h. Gel permeation chromatography was used for analysis. The chromatographic columns were Plael 10 μm MIXED-B (300 × 7.5 mm) and Plael 5 μm MIXED-D (300 × 7.5 mm). The column temperature was 80 °C, the injection volume was 100 μL, the mobile phase was 0.5% LiBr / DMSO, the flow rate was 0.5 mL / min, and the elution gradient time was 80 min. Data were analyzed using ASTRA 6.1 (Wyatt Technology) software.

[0059] 3. Determination of Degree of Polymerization of Modified Starch: Accurately weigh 10 mg of modified starch, resuspend it in 5 mL of deionized water, heat in a boiling water bath for 60 min, and vortex intermittently to mix. Then add 50 μL of 0.6 M sodium acetate (pH 4.4), NaN3 (10 μL, 2% w / v), and 10 μL of isoamylase (1400 U) and incubate at 37 °C for 24 h. Add 0.5% (w / v) sodium borohydride solution, vortex to mix, and let stand for 20 h. Then take 600 μL and put it into a centrifuge tube, and dry it under nitrogen at room temperature. Add 30 μL of 1 M NaOH to dissolve for 60 min, then add 570 μL of deionized water to dilute, centrifuge at 6000 × g for 5 min, and take the supernatant for analysis. The modified starch was analyzed and detected using a Thermo ICS5000+ ion chromatography system. The chromatographic column was a Dionex™ CarboPac™ PA200 (250*4.0 mm, 10 μm), with an injection volume of 5 μL. Mobile phase A consisted of 0.2 M NaOH; mobile phase B consisted of 0.2 M NaOH / 0.2 M NaAC. The column temperature was 30 °C. Components were analyzed using an electrochemical detector. The flow rate was 0.4 mL / min; the elution gradients were: 0 min A / B (90:10 v / v), 10 min A / B (90:10 v / v), 30 min A / B (40:60 v / v), 50 min A / B (40:60 v / v); 50.1 min A / B (90:10 v / v); 60 min A / B (90:10 v / v). Data processing was performed using Chromeleon 7.2 CDS software.

[0060] 4. Determination of branching degree of modified starch: 20 mg of modified starch sample was dispersed into an NMR glass tube containing 0.6 mL of anhydrous deuterated dimethyl sulfoxide solution. After thorough mixing, the sample was placed in an 80℃ water bath and shaken at 180 rpm for 48 h until the solution became clear and transparent. The NMR spectrometer parameters were set as follows: 400 MHz, 25℃, acquisition time of 10 s, cycle delay of 30 s, n=16 scans, with the residual DMSO signal peak as the internal reference. Peak analysis was performed using MestReNova 5.3.1 software.

[0061] 5. Determination of Gelatinization Characteristics of Modified Starch: The gelatinization characteristics of rice flour mixed with different modified starches were determined using a rapid viscosity meter. 3.0 g of modified starch sample was weighed and placed in the sample cell, 25 mL of distilled water was added, and the mixture was stirred before testing. The test procedure was as follows: initial rotation speed of 960 r / min, maintained for 10 s, then the rotation speed was reduced to 160 r / min, and the temperature was heated to 50℃ at a rate of 10 ℃ / min; held at 50℃ for 1 min; then the modified starch sample was further heated to 95℃ at a rate of 12℃ / min and held for 2.5 min; finally, the modified starch sample was cooled to 50℃ at a rate of 12℃ / min and held for 2 min. All gelatinization parameters were recorded.

[0062] 6. Determination of the thermodynamic properties of modified starch: 25.0 mg of modified starch sample and 25 μL of deionized water were placed together in an aluminum box and sealed using a tablet press. An empty box was set as the blank control group. The differential scanning calorimeter measurement program was set as follows: starting temperature 20℃, held for 1 min, and then increased to 150℃ at a rate of 5℃ / min. The initial temperature (To), peak temperature (Tp), termination temperature (Tc), and gelatinization enthalpy (ΔH) of the sample gelatinization were obtained.

[0063] 7. Determination of rheological properties of modified starch: Take out the sample prepared by the rapid viscosity meter in step (5) and place it on the parallel plate of the rheometer with a diameter of 60 mm. The fixed spacing is 1 mm. Apply silicone oil to the edge of the clamp to prevent moisture evaporation. Before measurement, set the test temperature to 25℃. Equilibrate the sample on the parallel plate for 2 min. Perform frequency scanning measurement in the range of 0.1-10 Hz under 1% constant deformation. Record the changes of the elastic modulus (G'), viscous modulus (G") and loss coefficient (tanδ=G” / G') of the sample during the frequency scanning process. A total of 21 detection points are recorded.

[0064] 8. Determination of hydration properties of modified starch: Prepare a 50 mL centrifuge tube, add 25 mL of ultrapure water and 800 mg of modified starch, denoted as W, shake thoroughly, and place in a 25℃ water bath for 5 min. Then, shake in a 95℃ constant temperature water bath for 30 min, remove and let stand at 25℃ for 5 min, then centrifuge at 2500 × g for 20 min. Take the supernatant, transfer it to a clean aluminum box, and dry it in a 105℃ forced-air drying oven until the weight is constant, denoted as W1. The weight of the precipitate is W2. Calculate the solubility S and swelling power SP, as follows:

[0065] ;

[0066] .

[0067] 9. Determination of short-range ordered structure of modified starch: Modified starch and potassium bromide were weighed at a mass ratio of 1:100, thoroughly ground and pressed into thin slices, and then tested using a Fourier transform infrared spectrometer with a scanning range of 400-4000 cm⁻¹. -1 Using OMNIC 9.2 software, the values ​​of 10⁴⁷ / 10²² cm⁻¹ were calculated respectively. -1 and 1022 / 995 cm -1 The ratio of absorption peak intensities.

[0068] 10. Determination of Crystallization Characteristics of Modified Starch: The crystal structure of the modified starch samples was analyzed using X-ray diffraction. The measurement conditions were CuKα radiation, voltage 40 kV, current 30 mA, scan rate 5° / min, scan range 5–50° (2θ), step size 0.02°, divergence peak 1°, anti-divergence peak 1°, and receiving slit 0.2 mm. The X-ray diffraction patterns were analyzed using Jade 6.5 software, and the crystallinity was calculated.

[0069] 11. Morphology determination of modified starch granules: The modified starch sample was fixed onto a circular substrate using double-sided conductive tape, and the substrate was subjected to gold plating under vacuum for 30 min. The microstructure of the modified starch sample was observed using a scanning electron microscope at different magnifications with a voltage of 5.0 kV.

[0070] 12. Storage stability of modified starch: The moisture content of modified starch samples was determined by the direct drying method according to GB 5009.3-2016 "National Food Safety Standard - Determination of Moisture in Food". Accurately weigh 2.000–5.000 g of uniformly pulverized modified starch and place it in a pre-dried weighing bottle to constant weight. Accurately record the total mass of the modified starch sample and the weighing bottle. After opening the weighing bottle, place it in a constant temperature drying oven at 103±2℃ for 4 h. Immediately after removal, re-cap and place in a desiccator to cool to room temperature before weighing. Continue drying and weighing every 1 h until the difference between two consecutive weighings does not exceed 2 mg, which is considered to have reached constant weight. Calculate the moisture content based on the difference in mass before and after drying. Three parallel samples were prepared for each sample, and the average value was taken.

[0071] 13. Determination of Fatty Acid Value in Modified Starch: The fatty acid value was determined by titration according to GB / T 5510-2024 "Grain and Oil Inspection: Determination of Fatty Acid Value of Grains and Their Products". Accurately weigh 10.0 g of pulverized and sieved modified starch sample and place it in a stoppered conical flask. Add 50 mL of anhydrous ethanol and extract by shaking in a constant temperature shaker for 30 min. After extraction, filter through rapid filter paper to obtain a clear extract. Accurately transfer 25 mL of the extract to a conical flask, add 2-3 drops of phenolphthalein indicator, and titrate with 0.01 mol / L potassium hydroxide standard titrant until the solution turns slightly red and remains so for 30 s. Record the volume of standard solution consumed. A blank control experiment was set up to eliminate reagent error. Calculate the fatty acid value of the sample based on the titration data. Three parallel experiments were set up for each modified starch sample, and the average value was taken.

[0072] Performance test results

[0073] 1. Analysis of the composition and structure of modified starch

[0074] The regulatory effects of PUL and PUL-TG enzymatic hydrolysis on the amylose and amylopectin content of corn starch are shown in the attached figure. Figure 1 As shown, corn starch contains 26% amylose and 74% amylopectin. After PUL debranching treatment for 4 h, 6 h, and 8 h, the amylose content increased to 33%, 41%, and 39%, respectively, significantly higher than the original corn starch, while the amylopectin content decreased accordingly. The increase in amylose was most significant at PUL-6 h, indicating that the enzymatic hydrolysis process reached its peak at this time. However, after extending to 8 h, the apparent amylose content slightly decreased, presumably because the excessively long hydrolysis time caused some of the already generated amylose molecules to be non-specifically hydrolyzed by PUL, or slight recombination between starch molecules, resulting in a decrease in amylose content.

[0075] Unlike single-enzyme modification, after 2 h, 6 h, and 10 h of PUL-TG enzymatic hydrolysis, the amylose content significantly decreased to 27%, 24%, and 18%, respectively, while the amylopectin content increased to 73%, 76%, and 82%. This is consistent with the catalytic function of TG, which can cleave α-1,4-glycosidic bonds and primarily catalyze the formation of new α-1,6-glycosidic bonds in starch segments, rebranching the linear chains generated by PUL debranching and connecting them with longer chains to form new linear starch chains. With prolonged reaction time, the degree of rebranching intensifies, leading to an increase in the proportion of branched structures and a continuous decrease in apparent amylose content. The results indicate that PUL debranching effectively enhances the linearity of starch molecules, while TG rebranching has the opposite effect, forming structures with a higher degree of branching. The combined action of the two enzymes regulates the composition and structure of corn starch.

[0076] 2. Analysis of modified starch chain length distribution results

[0077] The modified starch chain length distribution is shown in the attached figure. Figure 1 As shown in the figure. After complete debranching and separation by gel permeation chromatography, three different components were observed in starch. The first peak area (Peak 1) corresponds to the short linear chains derived from amylopectin, the second peak area (Peak 2) corresponds to the medium and long linear chains of amylopectin, and the third peak area (Peak 3) corresponds to the linear chains of amylose. The proportion of linear chains of amylose in the modified starch was PUL-6 h > PUL-8 h > PUL-4 h > PUL-TG-2 h > PUL-TG-6 h > PUL-TG-10 h, consistent with the trend of its amylose content. After PUL debranching treatment, the proportion of short amylopectin chains decreased with increasing enzymatic hydrolysis time, decreasing to 52.78%, 48.82%, and 48.91% in the PUL-4 h, PUL-6 h, and PUL-8 h groups, respectively, while the proportion of short amylopectin chains increased after PUL-TG treatment, reaching 52.55%, 60.46%, and 63.37%, respectively. In comparison, the overall proportion of long chains decreased with increasing enzymatic hydrolysis time.

[0078] 3. Analysis of the Degree of Polymerization Results of Modified Starch

[0079] The degree of polymerization of modified starch is shown in Table 1. Different enzymatic modification methods significantly affect the degree of polymerization of CS (Cytoplasmic Saccharide). P <0.05). In CS, the proportions of short-chain A (DP 6-12), medium-chain B1 (DP 13-24), medium-to-long-chain B2 (DP 25-36), and long-chain B3 (DP≥37) were 29.18%, 42.75%, 16.02%, and 12.05%, respectively, with an average chain length of 20.64 DP. After PUL treatment, the proportion of short-chain A showed a continuous decreasing trend with the extension of enzymatic hydrolysis time, decreasing to 27.93%, 26.57%, and 26.13% in the PUL-4 h, PUL-6 h, and PUL-8 h groups, respectively. The proportion of medium-chain B1 increased significantly, reaching 43.99%, 45.32%, and 45.81%, respectively. The proportions of B2 and B3 did not change significantly, and the average chain length increased to 21.60 DP, all significantly higher than that of native starch. After PUL-TG treatment, the proportion of short chain A continued to increase with the extension of enzymatic hydrolysis time, reaching 30.22%, 31.45%, and 32.83% in the PUL-TG-2 h, PUL-TG-6 h, and PUL-TG-10 h groups, respectively. Meanwhile, the proportions of medium- and long chain B2 and long chain B3 continued to decrease, with the proportion of B3 decreasing from 12.05% to 9.40%, and the average chain length continuously shortening to 19.38 DP.

[0080] The change in the degree of polymerization of corn starch after PUL modification stems from its specific hydrolysis of α-1,6-glycosidic bonds. After the branching sites of amylopectin are cleaved, some short linear chains originally attached to the main chain appear as apparent amylose, thus reducing the proportion of short chains and increasing the proportion of medium chains. Meanwhile, the proportions of medium- and long chains B2 and long chains B3 remain relatively stable as they are not specifically hydrolyzed by PUL. The increase in average chain length indicates that debranching increases the overall chain length of starch molecules. The average chain length in the PUL-4 h group reaches its maximum value and then slightly decreases. Due to the prolonged enzymatic hydrolysis time, some newly generated medium- and long chains undergo slight non-specific hydrolysis, resulting in a slight decrease in average chain length, but it is still significantly higher than that of corn starch. PUL-TG modification shows the opposite trend to single-enzyme modification. TG breaks down some medium- and long chains into short chains by cleaving α-1,4-glycosidic bonds, while simultaneously forming new α-1,6-glycosidic bonds to achieve rebranching. The proportion of short chain A increases significantly, while the proportions of medium- and long chain B2 and long chain B3 decrease due to continuous hydrolysis. The proportion of B1 slightly increases and then decreases in the early stage of complex enzymatic hydrolysis, indicating that some short chains polymerize into medium chains during this stage. The continuous shortening of the average chain length is a direct manifestation of the shortening of starch molecules and is highly correlated with the continuous increase in branching degree. The branching effect of transglycosylase can significantly reduce the average chain length of starch and increase the proportion of short chains.

[0081] Table 1 Degree of polymerization of modified starch

[0082]

[0083] 4. Analysis of branching results of modified starch

[0084] The branching degree of the modified starch is shown in the attached figure. Figure 2 As shown, different enzymatic treatments have a significant effect on the branching degree of corn starch. P < 0.05). The branching degree of CS was 3.82%. After PUL treatment alone, the branching degree of the samples decreased significantly, with the PUL-4 h, PUL-6 h, and PUL-8 h groups decreasing to 2.30%, 1.61%, and 1.66%, respectively. The PUL-6 h and PUL-8 h groups were significantly lower than the CS and PUL-4 h groups, indicating that PUL significantly reduced the branching structure of corn starch. In contrast, after PUL-TG combined treatment, the branching degree of the samples continued to increase with the extension of reaction time, with the branching degrees of PUL-TG-2 h, PUL-TG-6 h, and PUL-TG-10 h being 4.08%, 4.32%, and 4.53%, respectively. The significant decrease in branching degree of the PUL group was mainly attributed to the specific cleavage effect of PUL on the α-1,6-glycosidic bonds of starch molecules. The original cluster-like branching structure in the amylopectin molecules was gradually dismantled, and more branches were converted into linear or weakly branched segments, causing the molecular topology to change from dendritic to linear.

[0085] The branching degree of PUL-TG composite treatment continued to increase, and the increase showed a significant time dependence, indicating that TG further played a rebranching role on the linear substrate formed by PUL pre-debranching. The branching degree of PUL-TG-2 h was higher than that of CS, indicating that TG effectively transferred the linear chain generated by PUL in a shorter time. As the reaction was extended to 6 h and 10 h, the branching degree continued to increase, indicating that new α-1,6-glycosidic bonds were continuously accumulated, and the starch molecule gradually transformed from a low-branched structure to a more dense high-branched structure. This trend is highly consistent with the results of a continuous decrease in apparent amylose content, a continuous increase in the proportion of A-chains, and a gradual shortening of the average chain length in the PUL-TG group.

[0086] 5. Analysis of the gelatinization characteristics of modified starch

[0087] The gelatinization curves of different modified starches are attached. Figure 3 As shown, both enzymatic hydrolysis techniques significantly altered the gelatinization characteristics of starch. The CS gelatinization curve exhibited typical characteristics of increased viscosity upon heating and stable viscosity upon heat preservation. During heating, the viscosity continuously increased with rising temperature to a peak range of 2500-3000 cP, subsequently maintaining a stable high viscosity. After PUL modification, the enzymatic hydrolysis time significantly regulated the gelatinized viscosity, and the fluctuation amplitude of the gelatinization curve decreased, with the gelatinized viscosity decreasing with increasing hydrolysis time. Peak viscosity, the maximum viscosity of starch during heating, was significantly lower in PUL-6 h corn starch than in native corn starch, while no obvious peak viscosity was observed in PUL-6 h and 8 h corn starch. This change was mainly influenced by the multi-scale structure of starch; the destruction of starch granules and the reduction of ordered structure led to a decrease in viscosity. Simultaneously, the increase in amylose content also resulted in a decrease in peak viscosity, possibly due to the lower water-holding capacity of amylose compared to amylopectin.

[0088] The PUL-TG group had a more significant impact on gelatinization properties, with the overall gelatinization viscosity dropping below 1000 cP and the curve showing no obvious peaks, maintaining a stable low-viscosity state throughout the process. The new branches induced by TG were mostly shorter segments. Although this increased the proportion of α-1,6-bonds and the local branching density, it reduced the average molecular chain length and the ability of long chains to entangle, making the system more inclined to form compact and dispersed highly branched molecules rather than highly expanding, high-viscosity particles. PUL-TG-2 h already showed significantly lower viscosity, and the curve shape became flatter and viscosity buildup weaker after the reaction was extended, indicating that as rebranching proceeded, the number of long chains that could participate in expansion and viscosity buildup further decreased, and the molecular structure tended towards shorter chains and higher branching. After PUL debranching provided more reaction sites, TG catalyzed the reconstruction of glycosidic bonds in short-chain starch, changing the gelatinization mode by forming more compact branched molecules and a more uniform local structure. Therefore, its gelatinization curve showed low overall viscosity and a reduced peak-to-valley difference.

[0089] 6. Analysis of the thermodynamic properties of modified starch

[0090] The thermodynamic properties of PUL and PUL-TG composite modified corn starch are shown in Table 2. Different enzymatic modifications significantly altered the gelatinization heat conversion behavior of corn starch. P < 0.05). The initial gelatinization temperature represents the melting temperature of the ordered microcrystalline structure inside the starch granule, and ΔH reflects the amount of starch double helix that is unwound and melted during starch gelatinization. CS has the lowest To, indicating that starch granules require lower temperatures and energy to unwind the amylopectin double helix for gelatinization. In the PUL group, the To of PUL-6 h decreased to 78.24℃, lower than CS, indicating that debranching weakens some of the less stable ordered structures in the original granules, lowers the starch gelatinization initiation temperature, and promotes the gelatinization process; Tp decreased to 105.78℃, indicating that the stability of the dominant melting crystalline region decreased, and the granules were more easily thermally disintegrated; ΔH increased to 16.64 J / g, indicating that the total amount of fusible ordered structure did not decrease, possibly due to the rearrangement of linear chains generated by debranching to form a new double helix structure. The To of the PUL-8 h group increased to 92.37℃, significantly higher than CS and PUL-6 h groups, indicating that excessive debranching resulted in an ordered structure that was more difficult to initiate melting.

[0091] After enzymatic hydrolysis with PUL-TG, the To and Tp of PUL-TG-2 h starch were 67.06℃ and 98.17℃, respectively, significantly lower than other samples. In the early stage of complex enzymatic hydrolysis, the newly formed branched structures in the system had not yet fully established stable thermal response units, so the sample was prone to gelatinization and had the lowest main peak melting temperature. ΔH reached 16.33 J / g, indicating that although the stability of the crystalline region decreased, there were still many double helical or locally ordered structures that required endothermic destruction, possibly related to the rapid re-aggregation of short chains. As the time was extended to 6 h and 10 h, To rose back to 88.99℃ and 85.56℃, and Tc rose to 131.95℃ and 135.02℃, indicating that the rebranching gradually formed more uniform and complete structural units. The narrow Tc range indicated that the gelatinization temperature range of the complex enzymatically hydrolyzed starch was more concentrated and the gelatinization process was more synchronous, promoting uniform gelatinization during processing.

[0092] Table 2 Thermodynamic properties of modified starch

[0093]

[0094] 7. Analysis of the rheological properties of modified starch

[0095] The rheological properties of the modified starch are shown in the attached figure. Figure 4As shown. All samples exhibited a storage modulus G' higher than the loss modulus G” within the test range, and the loss factor tanδ was consistently less than 1, indicating that both natural starch and enzyme-modified starch pastes were dominated by elastic response, exhibiting typical characteristics of a weak gel system. In the PUL group, PUL-6 h showed a significantly higher G' across the entire angular frequency range than other samples, with G” also being the highest, while tanδ was the lowest in the low-frequency region, indicating the formation of a dense and stable three-dimensional network structure with the most pronounced elastic dominance. The G' values ​​of PUL-4 h and PUL-8 h were similar, both higher than CS, but significantly lower than PUL-6 h; PUL-4 h had the highest tanδ, indicating a stronger network structure than natural starch, but the viscous dissipative component was still relatively large. PUL-6 h exhibited the highest elasticity, possibly due to its higher amylose content and higher B1 chain ratio, without showing a loose structure or agglomerated imbalance, forming a continuous gel network.

[0096] The G' and G” values ​​of the PUL-TG group were higher than those of the CS group, while the G' and G” values ​​of the PUL-TG-6 h group were the highest in this group, and the tanδ value was the lowest. This indicates that moderate rebranching can also significantly enhance the system's elasticity. The source of this enhancement is not long linear chain entanglement, but rather the uniform network formed by highly branched molecules and the increase in local connection points. The G' value of the PUL-TG-10 h group was higher than that of the CS group, but lower than that of the PUL-TG-6 h group. At the same time, the tanδ value was higher than that of the 6 h group, indicating that excessive rebranching would result in excessively short chain segments and overly compact molecules, leading to insufficient effective chain entanglement length and no further enhancement of macroscopic elasticity. The complex enzyme treatment achieved an optimal balance between branching density, chain length, and molecular connectivity at a moderate reaction time. This phenomenon corresponds to the degree of polymerization results: PUL-TG-6 h has a high A-chain ratio, a low B3-chain ratio, and a moderate average chain length, which can provide more branching connection points without completely losing network bridging ability due to excessively short chain segments, thus exhibiting optimal rheological properties.

[0097] 8. Analysis of the hydration characteristics of modified starch

[0098] The results of the modified starch hydration properties are attached. Figure 5As shown, the solubility and swelling power of CS were 6.82% and 8.82 g / g, respectively. After PUL treatment, the solubility increased to 8.18%, 10.17%, and 10.03%, while the swelling power decreased to 7.27 g / g, 6.96 g / g, and 6.85 g / g. After PUL-TG treatment, the solubility decreased to 5.36%, 4.42%, and 4.03%, while the swelling power increased to 9.34 g / g, 10.92 g / g, and 11.13 g / g. The increase in solubility and decrease in swelling power caused by PUL treatment is related to the loosening of the particle structure and the increase in soluble segments after debranching of amylopectin. After the PUL enzyme cleaves the α-1,6-glycosidic bonds, some segments that were originally embedded in the branched clusters are transformed into shorter or medium-length linear molecules, which are more easily released from the particles into the continuous phase, thereby increasing the solubility. TG enzyme catalyzes the formation of highly branched amylopectin molecules, resulting in shorter molecular chain lengths and more uniform branch distribution. This structure enhances the ability of granules to retain water and maintain volume after absorbing water, thus increasing swelling power. However, the denser and more uniform network structure reduces the freedom of chain segments to dissolve outwards, leading to a decrease in soluble matter and solubility. Simultaneously, with prolonged PUL-TG reaction time, the swelling power of CS further increases, while solubility continues to decrease, indicating that as the degree of rebranching deepens, the ability of granules to absorb water and swell continues to increase, and fewer molecules dissolve. PUL-TG generates water-absorbing, swellable, and non-dispersible network units, allowing granules to absorb more water and maintain volume while releasing a small amount of soluble chain segments, thus exhibiting characteristics of low solubility and high swelling power.

[0099] 9. Analysis of Short-Range Ordered Structure Results of Modified Starch

[0100] The Fourier transform infrared spectra and short-range order of different modified starches are shown in the attached figure. Figure 6 As shown in the infrared spectrum, compared with CS, no new peaks appeared in the infrared characteristic absorption peaks of enzymatically hydrolyzed starch granules, indicating that enzymatic hydrolysis did not change the chemical bond composition of the starch granules. CS has peaks in the 1020-1047 cm⁻¹ range. -1 The characteristic peak shifted to 1045 cm⁻¹ after single enzyme modification. -1 The value was around 1000 cm⁻¹, while the modified compound enzyme redshifted to 1046 cm⁻¹. -1 A blue shift in peak position typically indicates weakened intramolecular hydrogen bonding in starch molecules, resulting in a looser structure in the crystalline regions; while a red shift and narrowing peak width reflect the reformation of intermolecular hydrogen bonds, leading to a more regular short-range ordered structure. In the complex enzymatic hydrolysis system, the transglycosylation effect of TG can reconstruct the connection mode of starch molecular chains, restoring the ordered arrangement of some crystalline regions and altering the structural disorder caused by PUL debranching. 3350 cm⁻¹ -1The broad peaks in the vicinity mainly correspond to OH stretching vibrations. Compared with CS, the broad peaks in the PUL group are generally flatter and have increased width, indicating that the debranching of PUL causes some α-1,6-bonds in amylopectin to break, exposing more hydroxyl groups and weakening the local association in the original relatively regular lamellar structure, thus making the hydrogen bond distribution more discrete; 2900 cm⁻¹ -1 The nearby CH stretching vibration peaks showed only slight shifts without substantial enhancement, indicating that the modification process did not induce significant hydrophobic framework reconstruction, but rather was dominated by changes in hydroxyl association. The PUL-TG sample showed a peak at 3350 cm⁻¹. -1 While maintaining a broad peak characteristic, the peak shape is relatively concentrated, indicating that TG further promotes the formation of short chain rearrangement and novel glycoside linkages on the basis of PUL debranching, making it easier for some linear short branches to approach and establish new intermolecular hydrogen bond networks, thereby improving the local structural compactness.

[0101] Starch hydrolyzed by PUL: 1047 / 1022 cm⁻¹ -1 The ratio shows a decreasing trend, 1022 / 955 cm -1 The ratio showed an increasing trend and continued to decrease with prolonged enzymatic hydrolysis time, indicating that PUL modification significantly weakened the short-range order of starch molecules. This may be because the debranching effect of PUL hydrolyzed the α-1,6-glycosidic bonds of amylopectin, disrupting the original branching arrangement of starch molecular chains and breaking the local order of the molecular chain arrangement. The short-range order of the PUL-8 h group reached its minimum value, consistent with the trend of its lowest relative crystallinity. After PUL-TG composite modification, the 1047 / 1022 cm⁻¹ of starch... -1 and 1022 / 955 cm -1 The ratios showed increasing and decreasing trends, respectively, indicating that PUL-TG modification significantly enhanced the short-range order of starch molecules. The new α-1,6 branches introduced by TG promoted the arrangement of local segments and double helices by generating more uniformly distributed short branches.

[0102] 10. Analysis of the thermodynamic properties of modified starch

[0103] XRD patterns and relative crystallinity of different modified starches are attached. Figure 7 As shown, all starches exhibited a typical A-type crystal structure with distinct diffraction peaks at 15°, 17°, 18°, 20°, and 23°. The crystal form of the modified starch was consistent with that of corn starch, indicating that although some crystalline structures in the starch granules were disrupted after PUL and TG modification, the crystal type remained unchanged. PUL treatment weakened the diffraction peak intensity, while PUL-TG composite modification enhanced it. This may be because the PUL hydrolysis process disrupted the crystal structure in the original starch, while TG treatment promoted the formation of new crystals.

[0104] Different enzymatic hydrolysis techniques showed different trends in their effects on the relative crystallinity (RC) of starch. With increasing PUL treatment time, the RC of CS (starch granules) decreased, while PUL-TG treatment significantly increased crystallinity. PUL treatment reduced the RC of CS from 21.40% to 18.51%, while with increasing TG treatment time, the RC increased to 21.58%, 22.13%, and 22.56%, respectively. Although linear chains with high molecular fluidity readily rearrange to form double helix structures, the PUL hydrolysis process disrupted the crystal structure in the original starch granules, leading to a decrease in relative crystallinity. Conversely, as the TG transglycosylation reaction proceeded, short branches with high branch density and relatively uniform distribution were formed in the starch structure, promoting intermolecular chain interactions and the formation of more double helix structures.

[0105] 11. Analysis of the microstructure of modified starch

[0106] Different enzyme modification methods significantly affected the surface structure and integrity of starch granules, as shown in the attached figure. Figure 8 As shown. After PUL single modification, a small number of shallow pits appeared on the surface of CS particles, and the number of pits increased with the extension of enzymatic hydrolysis time. The overall structure of the starch particles after PUL-4 h remained intact, with only a few tiny pits on the surface and no obvious breakage. The number of pits in the PUL-6 h and 8 h groups increased slightly, and the pit depth increased slightly, showing slight structural damage. When the enzymatic hydrolysis reached 8 h, starch agglomeration was obvious. PUL-TG treatment has a significant effect on starch particles, manifested as the appearance of pores. With the extension of TG treatment time, the number and size of pores increased, and the surface became increasingly rough. When the treatment time reached 6 h, some particles were destroyed; at 10 h, the intact structure of the starch particles was severely damaged, exacerbating the apparent breakage of starch, presenting as flaky, lumpy, and partially agglomerated phenomena, possibly due to excessively long enzymatic hydrolysis time. The starch particles treated with TG showed apparent damage, with some large and deep pores. The pits formed on the surface of starch granules by PUL treatment promote the action of TG, enabling it to act not only on the surface of the granules but also gradually penetrate into the interior of the granules, causing branching and increasing the number of amorphous regions. This leads to the destruction of the internal structure of the granules and the formation of pores. As the reaction time increases, the degree of structural damage on the surface and inside of the granules deepens, resulting in more and more pores on the surface of the starch granules and partial breakage of the starch granule structure.

[0107] 12. Storage stability of modified starch

[0108] The moisture content and fatty acid value of modified starch after 12 months of storage are shown in the attached figure. Figure 9As shown, all values ​​exhibit a slow upward trend. Moisture content increases rapidly from 0 to 6 months, with the growth rate slowing down from 6 to 12 months; fatty acid value increases steadily from 0 to 6 months, with the growth rate slowing down from 6 to 12 months. This modified starch demonstrates good short-term (within 12 months) storage stability and minimal deterioration in physicochemical quality.

[0109] Experimental Example

[0110] Rice noodles were prepared using PUL-modified starch and PUL-TG-modified starch prepared in Examples 1-3 and Comparative Examples 1-3, respectively, and their quality characteristics were determined.

[0111] Preparation method of modified starch-rice noodles:

[0112] Based on the total mass of rice flour, 3%, 5%, and 7% modified starch were added as experimental groups, while pure rice flour (RFRN) served as the control group. A twin-screw extruder was used to prepare the rice noodles. The temperatures of each zone of the twin-screw extruder were set as follows: zone one at 60℃, zone two at 95℃, and zone three at 90℃. After the equipment temperature reached the set value, the uniformly mixed raw materials were added to the hopper for extrusion. The extruded rice noodles were then suspended on stainless steel rods and placed in a constant temperature and humidity chamber at 15℃ and 70% relative humidity for 12 hours for aging. After aging, the rice noodles were transferred to a constant temperature drying chamber for 1 hour to obtain modified starch rice noodles.

[0113] 1. Cooking Quality Determination: Accurately weigh 3.0 g of modified starch rice noodles into a 250 mL beaker, add 100 mL of boiling water, and cook at a gentle boil for 4 min. After removing the rice noodles, cool the rice water to room temperature and filter it through filter paper. Accurately pipette 5 mL of the filtrate into a 50 mL volumetric flask, add 25 mL of distilled water, 1 mL of 0.1 mol / L hydrochloric acid solution, and 0.5 mL of iodine solution sequentially, and then dilute to the mark with distilled water. For the blank control, use 1 mL of 0.1 mol / L hydrochloric acid solution and 0.5 mL of iodine solution, and dilute to 50 mL with distilled water. Measure the absorbance at 620 nm using a UV-Vis spectrophotometer, with each sample measured in triplicate.

[0114] When determining the breakage rate, 15 rice noodles with a length greater than 20 cm were randomly selected from the sample to be tested, completely submerged in boiling water, steamed for 10 minutes, removed, filtered and rinsed with cold water for 1 minute, and then drained. The mass of rice noodles with a length greater than 10 cm (M1) and the mass of rice noodles with a length less than 10 cm (M2) were weighed respectively, and the breakage rate was calculated according to the following formula.

[0115] Broken strip rate / % = M2 / (M1 + M2).

[0116] For the determination of cooking loss rate, 600 mL of distilled water was added to a 1000 mL beaker and heated to boiling. Twenty rice noodles of uniform thickness and approximately 20 cm in length were randomly selected, and their initial mass (m1) was measured. After cooking the sample for 10 minutes, it was removed, rinsed with running water for 10 seconds, placed on filter paper to absorb surface moisture, and weighed (m2). It was then placed in an aluminum box and dried at 135℃ for 3 hours, and the mass after drying was measured (m3). The cooking loss rate was calculated using the following formula:

[0117] Cooking loss rate / % = (m1-m3) / m2.

[0118] 2. Texture Properties Determination: The texture properties of rice noodles were determined using a texture analyzer with a P / 35R probe. Three uniformly thick rice noodles, each 5 cm long, were randomly selected and arranged parallel to each other on the testing platform for each test. The test parameters were set as follows: speed before test 2.0 mm / s, test speed 1.0 mm / s, speed after test 2.0 mm / s, displacement 75 mm, compressive stress 50%, and trigger force 5.0 g. Each sample was tested five times, and the average value was taken. Six texture parameters of the rice noodles were measured: hardness, elasticity, adhesiveness, cohesiveness, chewiness, and resilience.

[0119] 3. Short-range ordered structure determination: The sample and KBr were mixed at a mass ratio of 1:100, thoroughly ground, and then pressed into thin slices. Fourier transform infrared spectroscopy was used for testing, with a scanning range of 400-4000 cm⁻¹. -1 Using OMNIC 9.2 software, the values ​​of 10⁴⁷ / 10²² cm⁻¹ were calculated respectively. -1 and 1022 / 995 cm -1 The ratio of absorption peaks.

[0120] 4. Determination of Crystallization Characteristics: The crystal structure of the rice noodle samples was analyzed using X-ray diffraction. The measurement conditions were CuKα radiation, voltage 40 kV, current 30 mA, scan rate 5 ° / min, scan range 5–50 ° (2θ), step size 0.02 °, divergence peak 1 °, anti-divergence peak 1 °, and receiving slit 0.2 mm. The X-ray diffraction pattern was analyzed using Jade 6.5 software, and the crystallinity was calculated.

[0121] 5. Microstructure determination: The rice noodle samples were fixed to a circular substrate using double-sided conductive tape, and the substrate was then subjected to gold plating under vacuum for 30 min. The microstructure of the samples was observed using a scanning electron microscope at a voltage of 5.0 kV and different magnifications.

[0122] 6. Sensory Characteristics Measurement: A sensory evaluation team of 10 evaluators with professional sensory evaluation training was invited to conduct sensory evaluation of the rice noodle samples. Sensory characteristics included color (0-10 points), odor (0-10 points), texture (0-10 points), consistency in soup (0-10 points), firmness (0-15 points), elasticity (0-15 points), stickiness (0-15 points), and smoothness (0-15 points). Each aspect was scored according to its suitability, and the sum of the scores was used as the final sensory score of the sample.

[0123] Experimental results

[0124] 1. Results of cooking quality test

[0125] The results are attached. Figure 10 As shown in Figures AC, the amount of starch modified with different enzymes significantly affects the cooking quality of extruded rice noodles (different letters indicate significant differences). P <0.05). Overall, the appropriate addition of modified starch can reduce the breakage rate and cooking loss, and lower or maintain the iodine blue value at a low level, indicating that the migration of soluble amylose / small molecule starch in the rice noodle system is inhibited and the structural integrity is enhanced during the cooking process. The cooking loss of rice noodles mainly comes from the precipitation of amylose and some soluble components from the gel network. The more amylose is released, the more turbid the soup becomes and the greater the loss. Amylose forms a blue complex with iodine, so the iodine blue value can be used as one of the indicators of the degree of amylose dissolution. The cooking loss rate and breakage rate of the control group rice noodles are relatively high, indicating that the soluble starch in the rice noodles is seriously lost during the cooking process and the structural stability is poor. For PUL modified starch extruded rice noodles (PUL-RN), the breakage rate and cooking loss do not change monotonically with the increase of modified starch addition. The breakage rate of rice noodles with 5% and 7% addition is relatively low. Among them, the cooking loss rate and breakage rate of the 5%-PUL-6 h group are the lowest, at 10.17% and 3.58%, respectively. This indicates that the linear chains generated after debranching are more likely to synergistically form a denser gel network with rice flour during extrusion cooking, improving shear and cooking resistance. However, under certain processing conditions, higher addition amounts can actually increase the breakage rate or cooking loss, possibly due to excessive short chains leading to rapid water absorption, gelatinization rheological imbalance, or network embrittlement. Consistent with the PUL-specific hydrolysis of α-1,6-bonds, which increases the proportion of linear chains and alters chain length distribution, moderate debranching is beneficial for network rearrangement and retrogradation reinforcement, while excessive debranching resulting in too many short chains weakens the backbone continuity and increases soluble components.

[0126] The overall cooking quality of rice noodles in the PUL-TG compound enzymatic hydrolysis group was superior to that of the PUL-only enzymatic hydrolysis group. Within a certain addition range, it exhibited a lower breakage rate and more stable cooking loss, indicating that the "rebranching-structural rearrangement" formed by the compound enzyme treatment is more conducive to constructing a continuous phase resistant to cooking breakage. TG enzymes can reduce the free migration of linear chains and enhance paste stability by transferring glycosyl groups, altering the α-glucan linkage mode, and increasing the degree of branching. This structure is more likely to interact with rice flour starch to form a uniform network, reducing starch dissolution and lowering the iodine blue value. The 3%-PUL-TG-6 h group showed the lowest cooking loss rate and breakage rate, decreasing from 14.46% and 6.88% to 9.03% and 0.87%, respectively, and also exhibited the lowest iodine blue value. The complex branched structure formed by the synergistic debranching and grafting of starch by the compound enzyme hydrolysis can form multiple cross-links with protein and starch molecules in rice flour, constructing a denser three-dimensional network structure, further improving the cooking resistance and structural stability of the rice noodles. However, when the addition amount was too high or the reaction time was too long (10 h), the cooking loss or iodine blue value rebounded in some samples, which is presumably related to the increased solubility of the composite modified starch and the increase of low molecular weight components, making them easier to precipitate during cooking. Appropriate addition can significantly reduce the breakage rate and cooking loss and inhibit the dissolution of amylose, while excessive addition may weaken the network synergistic effect.

[0127] 2. Effects of different modified starch additions on the textural properties of rice noodles

[0128] The textural properties of modified starch extruded rice noodles are shown in Table 3. Textural properties (hardness, adhesion, elasticity, chewiness, cohesion, and resilience) directly affect the palatability of the rice noodles. The results show that the addition of modified starch significantly improved the textural properties of the rice noodles. P < 0.05). The control group rice noodles had higher hardness, lower elasticity and chewiness, and moderate adhesion, indicating that traditional rice noodles were too hard and lacked elasticity. Rice noodles prepared with PUL-modified starch showed a trend of first increasing and then decreasing hardness with prolonged enzymatic hydrolysis time, while elasticity, chewiness, cohesion, and resilience gradually increased. The 7%-PUL-6 h group had the highest hardness, increasing from 1542.09 g to 1834.81 g, while the 7%-PUL-8 h group had the highest chewiness and cohesion. The short-chain molecules of PUL-modified starch can enhance the elastic network of starch paste, improving the elasticity and chewiness of rice noodles. The amylose formed by 6 h of enzymatic hydrolysis increases intermolecular interactions, improving the hardness of rice noodles. Excessive enzymatic hydrolysis (8 h) resulted in a slight decrease in hardness due to an excessive number of short-chain molecules.

[0129] Rice noodles prepared with PUL-TG modified starch exhibited superior textural properties. With prolonged enzymatic hydrolysis time, the hardness, elasticity, and chewiness of the rice noodles initially increased and then decreased. The 3%-PUL-TG-6 h group showed the highest elasticity, reaching 0.90; the 7%-PUL-TG-6 h group exhibited higher chewiness and cohesiveness, with a hardness of 1670.89 g and a chewiness of 955.38 g, significantly superior to the 2 h and 10 h groups with the same addition amount, and overall lower adhesion than the PUL group. The 7% addition amount generally resulted in higher hardness and chewiness than the 3% and 5% addition amounts, indicating that appropriately increasing the modified starch can enhance the structural strength of the rice noodles. The PUL-TG group maintained good elasticity even at a low addition amount (3%), demonstrating the more significant modification effect of the compound enzymatically hydrolyzed starch. The branched structure formed by the compound enzymatic hydrolysis forms a more stable cross-linked network with the rice flour matrix, giving the rice noodles a certain degree of gel strength and deformability. However, if the enzymatic hydrolysis time is too short (2 h), the starch molecules will not be sufficiently debranched and grafted, and a stable network structure cannot be formed, resulting in a lower texture index. If the enzymatic hydrolysis time is too long (10 h), the starch molecules will be excessively degraded, and the low molecular weight components will increase, leading to a decrease in gel network strength, hardness, and chewiness.

[0130] Table 3 Texture properties of modified starch extruded rice noodles

[0131]

[0132] 3. Effects of different modified starch additions on the short-range ordered structure of rice noodles:

[0133] The short-range ordered structure of modified starch extruded rice noodles is shown in the attached figure. Figure 11 As shown. The short-range ordered structure of rice noodles mainly characterizes the double helix and locally ordered stacking state of starch molecules in rice noodles, directly affecting the gel network stability and cooking quality of rice noodles. Its changes can be detected by Fourier transform infrared spectroscopy and 1047 / 1022 cm⁻¹. -1 With 1022 / 955 cm -1 The absorbance ratio is used to characterize the light intensity, where 1047 / 1022 cm⁻¹ is the absorbance ratio. -1 The higher the ratio, the stronger the short-range ordering. The samples were at 4000-500 cm⁻¹. -1 The infrared spectral curves within the range showed a generally consistent morphology, indicating that the rice noodle system retains the characteristic absorption peaks of typical starches. However, differences in peak position intensity and short-range order parameters suggest that the introduction of modified starch has a regulatory effect on the hydrogen bonding between starch molecules and the local ordered structure. (See attached...) Figure 11 As can be observed in Figures A and B, all samples are at approximately 3300 cm. -1A distinct absorption band appears at this location, primarily originating from the hydrogen bond structure formed by the stretching vibrations of the -OH groups in starch molecules. Upon addition of modified starch, the absorption peak in this region exhibits slight changes in shape and position shift. Compared to the control group RFRN, some samples show a slight redshift, with absorption peaks moving slightly towards lower wavenumbers, indicating enhanced hydrogen bonding and intermolecular interactions, leading to a decrease in the vibrational energy of the OH bonds. This suggests that the introduction of modified starch may promote the arrangement of starch chains into a more stable hydrogen bond network structure, thereby strengthening the intermolecular bonding of the rice noodle system.

[0134] With the appropriate addition of modified starch, rice noodles are more likely to form new locally ordered units during extrusion cooking, cooling, and aging, exhibiting enhanced short-range order. For PUL-modified starch extruded rice noodles (PUL-RN), the linear chains generated by moderate debranching are more likely to re-pair and form double helices during cooling, thus promoting the establishment of a short-range ordered structure. For PUL-TG-modified starch extruded rice noodles (PUL-TG-RN), the uniform short branches formed by moderate rebranching are conducive to the regular arrangement of local chain segments, forming more stable short-range ordered regions. PUL-RN group: 1047 / 1022 cm⁻¹ -1 The ratio increased with increasing addition amount, and was higher than that of RFRN. The ratio of the 7%-PUL-6 h group was the highest in the PUL group, while the ratio of 1022 / 955 cm⁻¹ was the highest in the RFRN group. -1 The ratio showed the opposite downward trend, indicating that the addition of PUL-modified starch increased the short-range orderliness of rice noodles. The PUL-TG-6 h group, due to its well-balanced branching degree, average chain length, and rheological properties, more easily formed a suitable number and uniformly distributed double-helix clusters in rice noodles, contributing to improved elasticity and cooking stability. However, when the TG reaction time was too long or the addition amount was too high, the chain segments became too short, and the local connection points were insufficient to support larger-scale orderly rearrangement, resulting in a slower increase in short-range orderliness, or even limitation due to local congestion and steric hindrance.

[0135] 4. Effects of different modified starch additions on the crystallization characteristics of rice noodles:

[0136] The crystallization characteristics of extruded rice noodles with different amounts of modified starch are shown in the attached figure. Figure 12As shown in the figure, all samples exhibited distinct diffraction peaks at 15°, 17°, 18°, and 23°, which are characteristic diffraction peaks of type A crystals. V-type diffraction peaks were also observed at 7.5°, 13°, and 20°, possibly due to the formation of starch-lipid complexes during extrusion. The crystallinity of the control group RFRN was 16.50%. In the PUL group, the RC (residual crystalline density) generally increased with increasing addition, ranging from 16.76% to 17.92%, with the 7%-PUL-6 h group reaching 17.92%, the highest among the PUL groups. In the PUL-TG group, the RC further increased to 16.06%-18.20%, with the 7%-PUL-TG-10 h group reaching 18.20%, the highest among all samples. The 7%-PUL-TG-6 h and 5%-PUL-TG-10 h groups also showed relatively high levels. This indicates that both modified starches promote the formation of more long-range ordered structures in rice noodles during extrusion and cooling, but the composite modified starch has a more significant promoting effect on crystallization structure at higher addition levels.

[0137] The increased RC in the PUL group is mainly related to the enhanced linear chain rearrangement ability after debranching. PUL treatment significantly increases the proportion of apparent straight chains and longer linear chains in corn starch. These chains are more likely to form double helices through intermolecular association after extrusion and aging, and further accumulate into ordered crystalline regions. After thermomechanical action destroys the original particle structure, the system is more prone to recrystallization during cooling and storage, ultimately resulting in a higher RC for PUL-RN than the control group. Studies have shown that the recrystallized structure formed during the cooling and aging process of rice noodles or rice starch gel is one of the key factors in improving hardness, elasticity, and resistance to overcooking. The greater increase in RC in the PUL-TG group indicates that the rebranched structure is more likely to promote the increase of long-range order. The significantly higher RC of PUL-TG modified starch compared to CS indicates that it forms a short-branched structure that is more conducive to local double helices and crystalline region accumulation, and is more likely to form a larger number of smaller ordered crystalline regions during extrusion. Therefore, the overall RC is higher than that of the control group and PUL-RN. Although the 7%-PUL-TG-10 h group had the highest crystallinity, its cooking quality and some texture indicators were not optimal. This indicates that when there are too many crystal regions or the chain segments are too short, a relatively rigid but unbalanced network may be formed, which limits the elasticity, resilience, or cooking stability of the rice noodles.

[0138] 5. Effects of different modified starch additions on the sensory scores of rice noodles

[0139] The sensory evaluation results of the modified starch extruded rice noodles are attached. Figure 13 As shown. The addition of different modified starches significantly affects the sensory quality of rice noodles. P <0.05), and its score change trend is closely related to the steaming and cooking characteristics, texture characteristics, color index and microstructure of rice noodles.

[0140] The control group rice noodles had the lowest overall sensory score, below 70 points. Specifically, the taste and chewiness scores were significantly lower, while the appearance and color scores were at a moderate level. This is mainly due to the high loss rate and breakage rate during steaming and cooking of the control group rice noodles, making them prone to breakage during consumption. They also had a softer texture, a slightly cloudy appearance, and a paler color, resulting in poor overall palatability. This is directly related to their loose microstructure and low degree of orderliness.

[0141] The sensory improvements in the PUL group mainly stemmed from its enhancement of texture and cooking integrity. The linear chains formed after debranching enhanced the hardness, chewiness, and structural stability of the rice noodles. Therefore, the samples were less prone to becoming mushy or breaking after cooking, resulting in a more chewy texture. Among them, the 5%-PUL-6 h-RN group achieved a sensory score of over 85 points, the highest among the PUL groups. The sensory score of the 3%-PUL-6 h group was lower than that of the 5% group because the addition amount was lower, and the modified starch did not significantly improve the quality of the rice noodles. Slight breakage of the rice noodles still occurred, and the texture and toughness were not significantly improved. When the addition amount increased to 7% and the degree of debranching was higher, the sensory score dropped. This was related to the molecular aggregation phenomenon in the microstructure. Too many linear chains led to excessive hardness of the rice noodles, making them difficult to chew. At the same time, they were accompanied by micro-cracks and decreased resilience, resulting in insufficient palatability and affecting overall acceptance. In addition, the sensory score of PUL-6 h-RN in the PUL group was significantly higher than that of PUL-4 h and PUL-8 h groups. This is because PUL-6 h is moderately debranched, and its structural features achieve a balance of various quality indicators. In contrast, PUL-4 h is not sufficiently debranched, and PUL-8 h is excessively debranched, both of which lead to an imbalance of some quality indicators and a decrease in sensory score.

[0142] The rice noodles prepared in the PUL-TG group had a better overall sensory score than the PUL group, with the 3%-PUL-TG-6 h group achieving the highest sensory score of over 90 points. The sensory scores of the 5% and 7% additions decreased slightly. The 3%-PUL-TG-6 h-RN group had the lowest cooking loss and breakage rate, maintaining a complete structure without breakage and exhibiting excellent toughness. Its textural properties were moderate, with slightly lower hardness and chewiness than the PUL group, but a more delicate and smooth texture, low adhesion, and no stickiness to teeth, resulting in a high palatability score. Furthermore, its color index was moderate, with brightness and yellowness meeting consumer visual preferences, resulting in a uniform appearance, no turbidity, and a bright color. Its microstructure was dense and uniform, with optimal continuity and integrity of the gel network, providing a structural foundation for its excellent taste and toughness. In addition, the sensory scores of the PUL-TG-6 h group in the PUL-TG group were significantly higher than those of the PUL-TG-2 h and PUL-TG-10 h groups. This is because the PUL-TG-6 h group achieved the best balance between branching density, chain length and molecular connection ability, and the various quality indicators were the most coordinated. In contrast, the PUL-TG-10 h group was over-branched, resulting in a softer texture and a slight decrease in toughness of the rice noodles, both of which affected the sensory scores.

[0143] In summary, modified starch can significantly improve the overall quality of extruded rice noodles, with PUL-TG composite modified starch at an addition rate of 3% and a debranching time of 6 hours exhibiting the best improvement effect. This treatment can effectively reduce the cooking loss rate and breakage rate of rice noodles, optimize the starch molecular structure and gel network formation, and give the rice noodles suitable hardness, elasticity, and chewiness, showing good application prospects.

[0144] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a modified starch ingredient for rice noodles with low breakage rate, characterized in that, Includes the following steps: (1) Starch is dispersed in sodium acetate buffer solution to prepare a starch aqueous suspension, gelatinization is completed, and the mixture is cooled to obtain starch paste; (2) Add pullulanase to the starch paste, stir and react for 4-8 h, heat in a boiling water bath for 10 min after the reaction is complete, and adjust the pH of the system with sodium hydroxide solution. (3) Add transglucosidase to step (2) and react for 2-10 h. After the reaction is complete, heat in a boiling water bath for 10 min to obtain inactivated starch liquid. (4) Add anhydrous ethanol to the inactivated starch liquid, stir and let stand at room temperature, then centrifuge, wash, freeze dry and grind to obtain the modified starch ingredient.

2. The preparation method of a modified starch ingredient for low-breakage rice noodles according to claim 1, characterized in that, The starch is one or more of corn starch, tapioca starch, potato starch, and mung bean starch.

3. The preparation method of a modified starch ingredient for low-breakage rice noodles according to claim 1, characterized in that, The sodium acetate buffer solution has a concentration of 0.02 mol / L and a pH of 5.

2.

4. The preparation method of a modified starch ingredient for low-breakage rice noodles according to claim 1, characterized in that, The gelatinization temperature is 100℃ and the gelatinization time is 40 min.

5. The preparation method of a modified starch ingredient for low-breakage rice noodles according to claim 1, characterized in that, In step (4), the centrifugation conditions are 3500 × g and centrifugation for 15 min.

6. The preparation method of a modified starch ingredient for low-breakage rice noodles according to claim 1, characterized in that, In step (4), anhydrous ethanol is used for washing, and the number of washing cycles is 3-5.

7. A modified starch ingredient for rice noodles with low breakage rate, characterized in that, The modified starch ingredient is prepared according to the preparation method described in any one of claims 1-6.

8. The application of the modified starch ingredient for rice noodles with low breakage rate as described in claim 7 in the food industry.

9. The application according to claim 8, characterized in that, The modified starch ingredient is added at a rate of 3% to 7% of the total mass of rice flour in the preparation of rice noodles with a low breakage rate.